A Hybrid MCDM Method Using Combination Weight for the Selection of Facility Layout in the Manufacturing System: A Case Study. (7th February 2020) - Zha, Shanshan; Guo, Yu; Huang, Shaohua; Wang, Shengbo
Abstract : Facility layout in the manufacturing system is an elaborate production activity since multiple, uncertain, and conflicting factors would affect facility layout decisions. Selecting the best facility layout among alternatives is considered as a problematic multicriteria decision-making (MCDM) problem. Generally, the facility layout is evaluated by the MCDM method with redundant factors, separate weights, and independent relationships between factors. To overcome this defect, this paper intends to propose a hybrid fuzzy MCDM method with combination weight (CW) based on integration with Delphi, fuzzy ANP, Entropy, and fuzzy PROMETHEE (CW-DFAE-FP) to select the most suitable facility layout alternative in an aircraft assembly workshop. The application results indicate that this method can effectively obtain the most suitable alternative for facility layout selection. Furthermore, the comparative analysis with other MCDM methods verifies the effectiveness of the proposed method and reveals the selection of weight has an impact on final priority ranking. Finally, sensitivity analysis highlights the performance of the proposed method and provides strategic insights to identify the critical criteria for the best alternative in facility layout.